Regulation on the Authority to Address the Determination of Village Head Election Results as the Object of State Administrative Disputes Has Not Been Based on Justice Value - Bernat Panjaitan; Anis Mashdurohatun; Sri Kusriyah (International Journal Labs, 2023)
As for the definition according to Law Number 5 of 1986 article 4, the State Administrative Court is one of the executors of judicial power for the people seeking justice for State Administrative disputes. Apart from the State Administrative Court, other courts as executors of judicial power in Indonesia based on Law Number 48 of 2009 concerning Judicial Power, are the General Court, the Religious Court and the Military Court which culminate in the Supreme Court, as well as an independent Constitutional Court. The type of research used in this research is analytical descriptive. Descriptive research is a form of research aimed at describing existing phenomena, both natural phenomena and man-made phenomena. Judges in being accountable for decisions often also seek support from jurisprudence and science. Seeking support in jurisprudence does not mean that a judge is bound by or has to follow decisions regarding similar cases that have been handed down by the Supreme Court and the Court of Appeal, or that have been decided by him alone. Based on the results of the research and discussion that have been described in the previous chapters, the authors draw conclusions, suggestions, from the results of the research as follows: Weaknesses in the regulatory authority adjudicating the Determination of Village Head Election Results as the Object of the Current State Administrative Dispute, Weaknesses Regulations in Article 1 number 8 and number 9 regarding the understanding of State Administrative Agencies or Officials and State Administrative Decisions in the perspective of current Human Rights, namely that there are weaknesses in the legal structure, legal substance and legal culture.